2017
DOI: 10.1177/0022487117742884
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural Matters: An Investigation of Key Assumptions of Multicultural Education Reform in Teacher Education

Abstract: Five decades of rhetoric and reform in teacher education underscore the importance of multicultural education in preparing teachers to meet the needs of all students. State and national policy initiatives targeting multicultural education build on two assumptions: first, that preservice teachers lack the multicultural awareness to function as culturally responsive educators, and second, that higher levels of multicultural awareness correspond with increased pedagogical proficiency. Few studies have examined va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 78 publications
0
77
0
5
Order By: Relevance
“…Pedagogical skills, especially in multicultural awareness are very much needed in developing professional madrasah teachers. Cherng & Davis's (2019) research findings suggested that educators who are responsive to culture can develop professional teachers.…”
Section: Discussionmentioning
confidence: 94%
“…Pedagogical skills, especially in multicultural awareness are very much needed in developing professional madrasah teachers. Cherng & Davis's (2019) research findings suggested that educators who are responsive to culture can develop professional teachers.…”
Section: Discussionmentioning
confidence: 94%
“…It is a precise duty of teachers of all kinds and degrees to be aware of this danger that undermines the root of the principles of acceptance and multiculturalism on which Europe is founded, since "efforts must be invested in implementing language learning programmes, additional support aids during schooling, and setting up schools and procedures that avoid ghettos as well as segregation" (Essomba, 2012, p. 137). Following this research, it is suggested that a pedagogical reform emerges in school programs where the voices of immigrants are really heard (Trueba and Bartolomé, 2000) and where there is specific teacher training that allows processes of deep self-reflection on their sense of diversity (Guo, Arthur and Lund, 2009) leading to more positive environments in the multicultural classroom (Cherng & Davis, 2019). Above all, this process is required to meet the following objectives promulgated by Frujas and Roxas (2016): (a) advancing the role of genuine cross-cultural relationships over traditional forms of cross-cultural competence in multicultural educational spaces and (b) abdicating the search for cultural authenticity implied in some multicultural education practice in favour of facilitating cultural agency for newcomer youth (p. 155).…”
Section: Discussionmentioning
confidence: 99%
“…Some scientists also emphasize the importance of the reformation of pedagogical education towards multicultural education in teachers' training for different educational institutions to meet the needs of all the students (Cherng & Davis, 2019).…”
Section: Problem Statementmentioning
confidence: 99%